The Role of visual-cues in children's wayfinding - Parreno, Pinky N. (2008)
Wayfinding is a skill people acquire as small children and develop as they age (Piaget, 1976). Thus stages on spatial knowledge acquisition and ultimately wayfinding are different for adults and children. Studies have shown that on navigating through unfamiliar environments children rely on landmarks more then adults do. The earliest stage of environmental cognition on children is limited to recognizing individual places in the landscape like a familiar building or park. Later they form a route pattern through motor movements and on the final stage children relate places to routes in a progressively more effective way until they have fully coordinated representation of the environment. This study is intended to determine the visual elements that children use as landmarks and further investigate the saliency of the qualities of these visual elements. This knowledge leads to improved design both on the overall spatial structure and the formgiving features for child friendly environments. Respondents between 7-11 years old undertook a specified trajectory search using slides taken from a local elementary school and were ask to describe their spatial experience. A choice-clue analysis was also performed to identify problem areas and elements that distort spatial cognition. Building elements such as stairs, windows, doors and columns with high differentiation showed a significant role in place identification and route learning as they were utilized as permanent markers on the route. The saliency of these markers was mainly attributed to their color, shape, size and material. Non-physical attributes like location, lighting quality and association to objects familiar to children also lead to landmark distinction. The result were used in formulating guidelines for the spatial configuration and architectural detailing of a children's art school day care center. The facility aims to provide a learning and recreational environment for children with the appropriate degree of complexity, user-control. Movement, comfort and safety.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2008